Self-Administration of Toluene Vapor in Rats - Braunscheidel, Kevin M.; Wayman, Wesley N.; Okas, Michael P.; Woodward, John J. (Frontiers in Neuroscience, 2020)
Inhalants, including volatile organic solvents such as toluene, continue to be one of the most prevalent, and often first substances abused by adolescents. Like other drugs of abuse, toluene affects the function of neurons within key brain reward circuits including the prefrontal cortex, ventral tegmental area and nucleus accumbens. However, preclinical models used to study these toluene-induced adaptations generally employ passive exposure paradigms that do not mirror voluntary patterns of solvent exposure observed in humans. To address this shortcoming, we developed an inhalation chamber containing active and inactive nose pokes, cue lights, flow-through vaporizers, and software-controlled valves to test the hypothesis that rats will voluntarily self-administer toluene vapor. Following habituation and self-administration (SA) training rats achieve vapor concentrations associated with rewarding effects of toluene, and maintain responding for toluene infusions, but not for air infusions. During extinction trials, rats showed an initial burst of drug-seeking behavior similar to that of other addictive drugs and then reduced responding to air SA levels. Responding on the active nose poke recovered during cue-induced reinstatement but not following a single passive exposure to toluene vapor. The results from these studies establish a viable toluene SA protocol that will be useful in assessing toluene-induced changes in addiction neurocircuitry.